THE ENVIRONMENT AND COLONIALISM IN JAMAICA KINCAID’S LUCY AND MY GARDEN (BOOK) - Wase , Anjeh (International Journal of Environmental Sciences, 2021)
This research paper sets out to show how Jamaica Kincaid, in her celebrated works, Lucy and My Garden (Book), intrinsically links the degradation of the environment to colonialism through memory even though most critics posit that men/women should preserve their environment. Purpose: To the protagonists, the environment brings back memory of subjugation and oppression that undermine man-nature relationship in Kincaid's selected works. Methodology: Qualitative research was used to write this paper since it involves textual analysis. Information of this research paper was gathered from the primary sources (Lucy and My Garden (Book) and secondary sources. Post colonialism and ecocriticism were deemed suitable theories on which this research paper could be hitched, in order to show how the environment is related to colonialism. The paper stresses on Kincaid's protagonists' hostility to the environment. In fact, whenever they see elements of the environment, they reflect on colonial trauma. Findings: The traumatic feeling from the characters under study stifles their relationship with the environment despite the fact that environmentalists and ecofeminists advocate for a close relationship with nature and its preservation in order to combat the current environmental crisis. Unique Contribution to Theory, Policy and Practice: This research, just like most environmentalists and ecofeminists will make people to understand that the natural environment is very vital to man and its preservation is a main concern for human beings. It will as well deepen discussion in the field of postcolonialism and ecocriticism. Readers of this article will help sensitize leaders of the world to stop colonialism so that the environment can be saved because traumatic memories are detrimental to the preservation of nature.